Etiological factors of the risk for occupational illness in nursing professionals: An etiology and risk review protocol - Cyntia Leenara Bezerra da Silva Gonzaga; Ana Clara Dantas; Bárbara Ebilizarda Coutinho Borges; Leandro Melo de Carvalho; Heloise Rosália de Carvalho Nascimento; Maria Clara Regis de Souza; Belo Mario Luis Generoso; Allyne Fortes Vitor (PLoS ONE, 2026)
Introduction Nursing professionals are inherently exposed to various risk factors, which may be exacerbated depending on the conditions under which care is provided. For instance, many healthcare institutions are considered hazardous environments for admitting patients with diverse diseases and performing procedures that carry potential risks of accidents and occupational diseases with them. Objective To identify the etiological factors associated with the Risk for Occupational Illness Nursing diagnosis in Nursing professionals. Methods An Etiology and Risk Review Protocol was developed following the guidelines outlined in the JBI Manual for Evidence Synthesis and registered in the International Prospective Register of Systematic Reviews under number CRD42024549181. Results The findings of this review will be publicly disseminated through scientific journals in health sciences, contributing to enhancing the evidence base corresponding to the Risk for Occupational Illness Nursing diagnosis. This will support its inclusion in future NANDA International editions, ensuring that the diagnosis remains current and aligned with the latest scientific literature. Conclusion It is anticipated that the review will generate evidence addressing stages 3, 4, 7, and 8 of the concept analysis for the Risk for Occupational Illness diagnosis, specifically: Identifying possible uses of the concept; Determining critical defining attributes; Identifying antecedents and consequences; and Defining empirical referents. Descriptors Occupational stress; Occupational diseases; Etiology; Nursing diagnosis; Nursing professionals